2023
DOI: 10.1002/smll.202207576
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Targeted and On‐Demand Non‐Coding RNA Regulation Nanoplatform against Metastasis and Recurrence of Triple‐Negative Breast Cancer

Abstract: Dysregulation of microRNAs (miRs) is the hallmark of triple‐negative breast cancer (TNBC), which is closely involved with its growth, metastasis, and recurrence. Dysregulated miRs are promising targets for TNBC therapy, however, targeted and accurate regulation of multiple disordered miRs in tumors is still a great challenge. Here, a multi‐targeting and on‐demand non‐coding RNA regulation nanoplatform (MTOR) is reported to precisely regulate disordered miRs, leading to dramatical suppression of TNBC growth, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…PEI with low molecular weight has the advantage of low cytotoxicity, but to improve its transfection efficiency, many studies have introduced special groups or cross-linked them to enhance transfection. [140][141][142][143][144] Dahlman et al modified low molecular weight PEI (PEI600) with alkyl chains to realize effective siRNA deliver. 145 Guan et al synthesized fluorocarbon (FC) modified PEI600 for that purpose.…”
Section: Polymer Polyethylenimine (Pei)-based Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…PEI with low molecular weight has the advantage of low cytotoxicity, but to improve its transfection efficiency, many studies have introduced special groups or cross-linked them to enhance transfection. [140][141][142][143][144] Dahlman et al modified low molecular weight PEI (PEI600) with alkyl chains to realize effective siRNA deliver. 145 Guan et al synthesized fluorocarbon (FC) modified PEI600 for that purpose.…”
Section: Polymer Polyethylenimine (Pei)-based Nanotechnologymentioning
confidence: 99%
“…Compared to low molecular weight PEI, high molecular weight PEI often exhibits better transfection effectiveness, however, often has higher cytotoxicity. PEI with low molecular weight has the advantage of low cytotoxicity, but to improve its transfection efficiency, many studies have introduced special groups or cross‐linked them to enhance transfection 140–144 . Dahlman et al modified low molecular weight PEI (PEI600) with alkyl chains to realize effective siRNA deliver 145 .…”
Section: Nanotechnology‐based Delivery Of Crispr/cas9mentioning
confidence: 99%
“…555 A large number of nuclear targeting NPs had been developed. 210,535,[556][557][558][559][560][561][562][563][564][565][566][567][568][569][570] For example, Ping et al 535 proposed a solution that could target the nucleus and expand the nuclear pores. On this basis, the solution was combined with a size reduction strategy, the in vitro and in vivo results showed that it could effectively enhance nuclear uptake and promote the delivery of nuclear-targeted anticancer drugs.…”
Section: Nucleus Targetingmentioning
confidence: 99%
“…Therefore, it is necessary to construct a transport vector with nucleus targeting function to effectively deliver drugs 555 . A large number of nuclear targeting NPs had been developed 210,535,556–570 . For example, Ping et al 535 proposed a solution that could target the nucleus and expand the nuclear pores.…”
Section: Drug Delivery Strategies Using Nps For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation